Exploring the antibacterial and anti-biofilm properties of Diacerein against methicillin-resistant Staphylococcus aureus - Sun, Yingying; Wu, Yaozhou; Chang, Yanbin; Sun, Gaoling; Wang, Xin; Lu, Zhangping; Li, Keke; Liang, Xiaofang; Liu, Qianqian; Wang, Wenjie; Wei, Lianhua (Frontiers in Microbiology, 2025)
BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) poses a significant clinical challenge due to its multidrug resistance. Diacerein (DIA), primarily used to treat degenerative joint diseases, has recently been found to exhibit antibacterial activity, though its specific antibacterial mechanisms remain unclear.MethodsThe minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of DIA, as well as in - vitro combination susceptibility testing, were determined using the broth microdilution method. Additionally, resistance induction assays, time-growth curve measurements, membrane fluidity, intracellular protein levels, and reactive oxygen species (ROS) were assessed. The inhibition and clearance of MRSA biofilms by DIA were evaluated using the crystal violet staining method, with bacterial morphology and biofilms observed via scanning electron microscopy and confocal laser scanning microscopy. Finally, transcriptome analysis was conducted to identify gene expression changes in MRSA treated with DIA, and RT-qPCR verification was performed.ResultsThe MIC and MBC of DIA against MRSA were 32 μg/mL and 128 μg/mL, respectively, and synergistic antibacterial effects when combined with ampicillin. DIA increased intracellular ROS levels and membrane fluidity in MRSA, decreased soluble protein synthesis, and altered bacterial morphology. Additionally, DIA significantly inhibited MRSA biofilm formation and disrupted pre - existing biofilms. Transcriptome analysis revealed 1,045 differentially expressed genes between the DIA-treated group and the control group, primarily involving pathways such as the tricarboxylic acid cycle, phosphorylation, ribosome metabolism, and nucleotide metabolism.ConclusionIn summary, DIA has antibacterial and anti-biofilm activities against MRSA and does not easily induce resistance. Its antibacterial mechanisms may involve multiple aspects, including bacterial protein synthesis, energy metabolism.